Correction of the Photovoltaic System Control by the Addition of a Voltage Regulator in the Electrical Conversion Chain - Ali Ghelam; Mohamed Boudiaf; Yazid Derouiche (Majlesi Journal of Electrical Engineering)
The objective of this work is to meet the variations of the electrical energy needs by modifying the conventional topology of the conversion chain, at the same time to improve the operation of the photovoltaic system. This article focuses on improving the performance and efficiency of photovoltaic systems connected to the AC grid, through the use of advanced control algorithms (Sliding Mode control SMC and Fuzzy Logic Control FLC) for the control of DC/DC and DC/AC power conditioners. The control of the DC/DC converter allows the pursuit of the maximum power point MPPT of the photovoltaic generator with a view to a better utilization of the photovoltaic generator. The inverter control system is used to inject synchronized sinusoidal output current to the power grid and to improve the quality of energy injected into the grid. The original idea of this work is based on the insertion of a DC/DC BOOST voltage regulator in the conversion chain (between the battery and the inverter) to adjust the voltage transfer of the DC bus. This technique allows the provision of AC voltage for the sufficiency of the energy required by the control according to the need of the load.